Activation of wheat seed germination under drought and salt stresses by γ-aminobutyric acid priming: Relationship with changes in ROS generation and osmolyte content - Ivan V. SHAKHOV; Liana I. RELINA; Maryna A. PYSHCHALENKO; Yuriy E. KOLUPAEV (Notulae Scientia Biologicae)
γ-Aminobutyric acid (GABA) is currently considered as one of the important stress metabolites capable of regulating plant tolerance to adverse factors by being involved in the functioning of cellular signaling pathways. Data on positive effects of GABA on tolerance to abiotic stresses were obtained on different plants. However, until now there was no information on the effects of seed priming, including short-term treatment with GABA solutions followed by drying, on the germination of wheat (Triticum aestivum L.) caryopses and growth of seedlings under drought and salt stress, which defined the purpose of this study. A significant increase in the germination energy and germination rate of seeds primed with 0.5 mM GABA was found under simulated drought (15% PEG 6000) or salt stress (150 mM NaCl). In addition, GABA priming mitigated declines in biomass accumulation and tissue hydration in stressed seedlings. The seed germination under drought or NaCl exposure was associated with a sharp increase in the guaiacol peroxidase activity, enhanced generation of superoxide radical and hydrogen peroxide, and accumulation of lipid peroxidation products. GABA treatment significantly reduced these manifestations of oxidative stress, especially under simulated drought. We noted a decrease in the soluble carbohydrate content and an increase in the proline content in shoots subjected to osmotic or salt stress. Seed treatment with GABA maintained the sugar amount in stressed shoots close to the control level, but had a little effect on the proline content. There were strong positive correlations between sugar content in seedlings and germination rate and between sugar content and biomass accumulation. A strong negative correlation between sugars and oxidative stress markers indicated that GABA-induced enhancement of soluble carbohydrate accumulation in seedlings was important for tolerance to osmotic stress. We concluded that it was possible to use GABA priming as a tool to increase the germination rate of wheat seeds and tolerance of plants during early ontogeny stages under drought and salt stresses.